2010
DOI: 10.1002/hrm.20332
|View full text |Cite
|
Sign up to set email alerts
|

When do high‐level managers believe they can influence the stock price? Antecedents of stock price expectancy cognitions

Abstract: Stock based rewards are often used to motivate high-level managers to take actions to increase the stock price of the fi rm. However, numerous constraints may weaken the perceived link between individual effort and stock price appreciation for many recipients. This study introduces a new construct, stock price expectancy, which we defi ne as individuals' perceptions of infl uence over their fi rm's stock price. We examined its antecedents in a sample of 349 high-level U.S. managers and found that employment at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…This effect was especially true in the 1990s as the proportion of SOs reached one-third of total managerial compensation (Hall and Liebman, 1998; Murphy, 1999). Similar results were observed in 2000s when SOs became the largest single component of top management rewards (Dunford et al , 2010; Hall and Murphy, 2002), and nearly half of all Fortune 100 companies offered SOs (Ericson, 2004; Hempel and Fay, 1994).…”
Section: Introductionsupporting
confidence: 70%
“…This effect was especially true in the 1990s as the proportion of SOs reached one-third of total managerial compensation (Hall and Liebman, 1998; Murphy, 1999). Similar results were observed in 2000s when SOs became the largest single component of top management rewards (Dunford et al , 2010; Hall and Murphy, 2002), and nearly half of all Fortune 100 companies offered SOs (Ericson, 2004; Hempel and Fay, 1994).…”
Section: Introductionsupporting
confidence: 70%
“…Specifically, contingent pay should increase the belief in control over the supplier selection situation. Dunford et al () recently found that contingent pay (i.e., offering stock options) positively influences perception of control (i.e., the expectancy that effort will influence stock performance), regardless of one's ability to control the situation. This implies that Shapira's () postdecisional control concept can be integrated with BAM.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Stock price as an indicator to measure the success of a company's management, where market power on the stock market is indicated by the sale and purchase of the company's shares in the capital market (Cao et al, 2002;Dunford et al, 2010;Fu et al, 2020 ;Yin et al, 2020). The transaction conditions and conditions are based on investors' observations of the company's achievements in increasing profits.…”
Section: Introductionmentioning
confidence: 99%